A unified theory for microstructural alterations in bearing steels under rolling contact fatigue. (15th August 2018) - Fu, Hanwei; Rivera-Díaz-del-Castillo, Pedro E.J.
Abstract: Three major types of microstructural alterations occurring under rolling contact fatigue, white etching areas (WEAs), dark etching regions (DERs) and white etching bands (WEBs), are modelled under a unified approach: dislocation-assisted carbon migration theory. Following our previous work on DERs and WEBs, a novel model is proposed to describe dislocation cell formation in WEAs. The proposed model yields predictions of WEAs appearance, agreeing with experimental observations. Bearing life can be estimated by the WEA appearance model. The three microstructural alterations models are combined and, for the first time, it becomes possible to predict the occurrence and the formation progress of WEAs, DERs and WEBs with a unified theory. Microstructural alteration maps are plotted as a function of number of cycles, temperature, contact pressure and stress cycle frequency. The models are validated by the experimental results reported over the last 50 years. Graphical abstract: Image 1